Bioremediation potential of industrial laundry effluent by agaricomycetes from brazilian tropical dry forest (Research, Society and Development, 2022)
Mycotic bioremediation of effluents from industrial jeans laundries is a necessary biotechnological treatment to prevent contamination of water bodies. In phase I, the discoloration of Indigo Carmine Dye (ICD) and Textile Effluent (TE) by seven species of Agaricomycetes from the brazilian tropical dry forest (Caatinga) was evaluated. First, nutritional stress was caused by Nitrogen Limitation (NL) at three experimental times, T1 (1 day). T2 (4 days) and T3 (7 days). In phase II, microorganisms were cultivated in the initial growth times Gi1 (10 days) and Gi2 (25 days), Without Addition of Nutrients (WAN) and stress was induced by NL (T1). Subsequently, ICD and TE discoloration tests continued for 28 days. In the ecotoxic analysis, the biotreated samples in phase II were tested on nauplii of Artemia HIGH 5 without the addition of food. In phase I, the percentages of ICD and TE discoloration were greater than 55% using fungi F1, F2, F5 and F6 for 10 days without sterility. In phase II, the best percentages of discoloration were found for TE in Gi1 and for ICD in Gi2, with F1 and F5 (identified by molecular biology). The results showed that Gi1 (WAN) increased the biodegradation of TE and Gi2 (WAN) favored the biodegradation of ICD, in T1 (NL) without sterility. The best enzymatic activity of laccase and lignin peroxidase was presented in F5. The enzyme extracts had a Michaelis-Menten kinetic behavior. All samples of TE bioremediated in phase II no showed toxicity on Artemia sp. in 48 hours of experimentation.